'Yes I understand': language choice, question formation and code-switching in interpreter-mediated police interviews with victim-survivors of domestic abuse. (15th January 2021) - Tipton, Rebecca
ABSTRACT: This article presents the findings of the analysis of authentic interpreter-mediated police interviews with victim-survivors of domestic abuse with a focus on question formation and delivery, language choice and code-switching. It is set against the backdrop of the forces wide inspection of police response to domestic abuse in England and Wales and implementation of EU Directive EU/2012/29 establishing minimum standards on the rights, support and protection of victims. Drawing on conversation analysis and available police interview guidelines, I show how the voice of the victim-survivor can remain obscured even when professional language support provisions are in place, and shed light on interpreting practices that can limit an interviewing officer's ability to assess risk. I suggest that, while it may not be appropriate for interpreters to be present for the duration of the pre-interview planning phase, it offers a dynamic forum for negotiating approaches to challenges in victim-survivor interviews.